The global immune-nutrition-inflammation index predicts pathological response and survival in esophageal squamous cell carcinoma treated with neoadjuvant immunochemotherapy - Feng, Zhouxv; Yi, Huihan; Xiao, Jiazhou; Huang, Zhixin; Tu, Yifei; Liu, Bo (Frontiers in Nutrition, 2025)
ObjectiveThe global immune-nutrition-inflammation index (GINI) is a new composite indicator that assesses nutrition and inflammation and has been linked to prognosis in various cancers. Neoadjuvant immunochemotherapy (nICT) is becoming more common for treating locally advanced esophageal squamous cell carcinoma (ESCC). However, the potential of GINI to predict outcomes for ESCC patients undergoing nICT has not yet been explored. This study aims to examine the predictive value of the pretreatment GINI in relation to pathological response and prognosis for ESCC patients receiving nICT.MethodsA total of 138 patients with locally advanced ESCC who underwent nICT followed by radical resection at our institution between 2022 and 2024 were retrospectively included in this study. The GINI index was calculated from pretreatment blood parameters. The receiver operating characteristic (ROC) curve analysis was conducted to determine the optimal cutoff value of the GINI index for predicting pathological response, which was defined using the Becker tumor regression grade (TRG). Logistic regression and Cox proportional hazards models were used to analyze the associations between the GINI index and both pathological response and survival outcomes.ResultsThe optimal cutoff value of GINI for predicting pathological response was 73.47 (AUC = 0.912). Multivariate analysis identified high-GINI as an independent risk factor for both poor pathological response (OR = 1.05, p < 0.001) and shorter overall survival (OS) (HR = 1.01, p = 0.012). Compared to the low-GINI group, patients in the high-GINI group had significantly poorer tumor differentiation, more advanced pathological stage, and a higher incidence of complications (all p < 0.05). Survival analysis demonstrated that the low-GINI group had significantly better 3-year OS (87.8% vs. 68.7%, p = 0.014) and disease-free survival (DFS) (82.7% vs. 63.3%, p = 0.011) than the high-GINI group.ConclusionPretreatment GINI is a promising biomarker for predicting pathological response and survival outcomes in locally advanced ESCC patients treated with nICT. A high GINI level is significantly associated with treatment resistance and poorer prognosis, suggesting its potential utility in risk stratification and guiding individualized treatment strategies.